2003
DOI: 10.1111/j.1574-6941.2003.tb01049.x
|View full text |Cite
|
Sign up to set email alerts
|

Marine bacterial organisation around point-like sources of amino acids

Abstract: To better understand the trigger for and use of motility in marine bacterial chemotaxis, specific (amino acids) chemical stimuli were used to test the effect on bacterial speed and reorientation. An assay system was developed to analyse bacterial behavioural responses to point-like nutrient sources (beads 10-40 mum). The marine bacteria Pseudoalteromonas haloplanktis, Shewanella putrefaciens, Deleya marina, the enteric bacterium Escherichia coli and an enriched assemblage of marine bacteria were used in the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 36 publications
4
49
0
Order By: Relevance
“…Simulation results show motile bacteria prefer to congregate at most favourable nutrient gradient consistent with experimental observations (Adler, 1966; Zhulin et al. , 1995; Fenchel, 2002; Barbara and Mitchell, 2003). High motility could potentially provide a means for rapid and uniform dissemination of bacteria in polluted environments (Witt et al.…”
Section: Resultssupporting
confidence: 84%
“…Simulation results show motile bacteria prefer to congregate at most favourable nutrient gradient consistent with experimental observations (Adler, 1966; Zhulin et al. , 1995; Fenchel, 2002; Barbara and Mitchell, 2003). High motility could potentially provide a means for rapid and uniform dissemination of bacteria in polluted environments (Witt et al.…”
Section: Resultssupporting
confidence: 84%
“…In addition to the familiar run-tumble mechanism seen in many bacteria, such as E. coli ( 32 ), H. pylori also tends to reverse its swimming direction, which has been related to chemotactic sensing and quorum sensing in earlier works ( 28 , 31 , 38 41 ). Such run-reverse swimming has also been seen in several marine bacteria that swim in highly viscous environments ( 42 – 45 ) and in Caulobacter crescentus ( 9 ). We were able to observe reversal events in both the helical and rod-shaped bacteria tracks swimming in BB10, as shown in Fig.…”
Section: Resultsmentioning
confidence: 72%
“…A heat dissipation ¢lter consisting of water in a container 3 cm thick was used to minimise the e¡ect of any temperature changes caused by the microscope lamp [6]. The video image was recorded continuously by a video cassette recorder with a frame speed of 24 frames s 31 (Panasonic NV-HS1000).…”
Section: Microscopymentioning
confidence: 99%
“…Typically, marine bacteria swim at much higher speeds, up to 400 Wm s 31 [11,12], than E. coli with maximum speeds of only 40 Wm s 31 [13]. Marine bacteria also exhibit a run and reverse strategy, which enables them to form tight ( 6 20 Wm wide) swarm bands around air bubbles or chemical attractants [4,6,14,15]. Based on this run and reverse behavior Luchsinger et al [16] developed a computer model, which showed that bacteria would be able to orient themselves around ¢xed point sources of nutrients in a shear ¢eld.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation